2009
DOI: 10.1128/mcb.01180-08
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase KIS Localizes to RNA Granules and Enhances Local Translation

Abstract: The regulation of mRNA transport is a fundamental process for cytoplasmic sorting of transcripts and spatially controlled translational derepression once properly localized. There is growing evidence that translation is locally modulated as a result of specific synaptic inputs. However, the underlying molecular mechanisms that regulate this translational process are just emerging. We show that KIS, a serine/threonine kinase functionally related to microtubule dynamics and axon development, interacts with three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 41 publications
(59 reference statements)
2
36
1
1
Order By: Relevance
“…Nevertheless, suggestively significant associations were identified in a region containing UHMK1, a gene that encodes the brain-enriched protein kinase KIS. Animal models suggest that UHMK1 is highly expressed in the brain, and knockdown of this gene effects the development of cortical neurons in culture [37]. In line with our findings, UHMK1 knockout mice display a distinct deficit in fear conditioning, which is accompanied by downregulation of genes implicated in the aetiology of anxiety and fear, including multiple components of GABA A receptors [38].…”
Section: Discussionsupporting
confidence: 83%
“…Nevertheless, suggestively significant associations were identified in a region containing UHMK1, a gene that encodes the brain-enriched protein kinase KIS. Animal models suggest that UHMK1 is highly expressed in the brain, and knockdown of this gene effects the development of cortical neurons in culture [37]. In line with our findings, UHMK1 knockout mice display a distinct deficit in fear conditioning, which is accompanied by downregulation of genes implicated in the aetiology of anxiety and fear, including multiple components of GABA A receptors [38].…”
Section: Discussionsupporting
confidence: 83%
“…However, cell biological and biochemical studies have identified RNA granule association with KIF5 (kinesin-1) and KIF3 (kinesin-2) in dendrites, KIF3C in axons, and kinesin-1 and dynein in Drosophila S2 cells [33], [34], [35], [36], [37]. A role for microtubule-dependent motor proteins in transporting mRNA is also consistent with reductions in mRNA localization within neurites following microtubule destabilization with colchicine [26], [38].…”
Section: Discussionmentioning
confidence: 79%
“…Not surprisingly, most of UHMK1-related functions have been addressed in the context of adult nervous system [6,8,[10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Since then it has been described to interact with a range of proteins, such as peptidylglycine α -amidating monooxygenase (PAM) [2]; cyclin dependent kinase inhibitor (CDKI) p27 KIP1 [3]; splicing factors SF1 [4] and SF3b155 [5]; components of the neuronal RNA granules NonO, KIF3A and eEF1A [6]; proliferation marker PIMREG [7]; and RNA-binding proteins CPEB1, CPEB2 and CPEB3 [8], shedding light on different functions of UHMK1 in diverse cellular processes.…”
Section: Introductionmentioning
confidence: 99%